Návrh na zefektivnění procesu obrábění vnitřního ozubení - Hoffmann, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Předmětem této studie je návrh na zefektivnění procesu výroby unašeče s vnitřním ozubením. V úvodu práce jsou popsány některé druhy ozubení. Druhá kapitola je zaměřena na rozbor vyráběného dílu a pracovišť pro výrobu. Třetí kapitola obsahuje popis technologických metod výroby ozubení konvenčními a nekonvenčními metodami. Praktická část práce obsahuje návrh inovace výrobního procesu výroby ozubení. V závěru je provedeno technicko–ekonomické zhodnocení včetně porovnání stávajícího a nově navržených řešení.

The subject of this study is a proposal to streamline the production process of gear with internal gear. At the beginning of the thesis are described some types of gearing. The second chapter is focused on the analysis of manufactured part and workplaces for production. The third chapter contains description of technological methods of gearing production by conventional and unconventional methods. The main point of this work is a proposal of innovation of the production process of gearing production. In conclusion, technical-economic evaluation including a comparison of existing and newly designed solutions.
Efficiency Improvement Proposal of Machining Process of Inner Gearing
Keywords: ozubené kolo; vnitřní ozubení; výroba ozubení; obrážení; Power Skiving; gear; internal gear; gear manufacturing; shaping; Power Skiving